(3cTa GdGdJHGS Yf ehLR CHj GdYHGSs - (3GdUjeQj, GdUjeQj, GdUjeQj, eadM Hf GdMSf Hf QTjO, J HYO (B873(3g` (B1468(3es ((3Ydj Hf eMeO GdMdjs)
(3ChdgG (B:s
(3ChdgG(B: (3Gddg CMeO Ydi ShGHZ CfYGeg hJQGOa BdGFg hEcQGeg (B... (3gPG dGcdGe eTJed Ydi eHGMK TQjaI hahGFO dWjaIs
(3BNQgG (B:s
(3BNQgG(B: (3hEf Hbj Ydi GdGSJMbGb Odg Cf jYWjg ZjQgG hjYWjgG YjQg hEf de jYWg ZjQgG hEf cGfJ TGI cGf ddabjQ QO GdbjeI aj Gdbjej hGdeKd aj GdeKdj(B. (3GfJgi UhQI cdGe GdeUfa, CQOfG EjQGOg aj gPG GdTQM YfO GfJgGA GdeTQhMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 281s
(3GdPQjYI, L (B18: 16s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis